Підготовка фахівців до роботи з дітьми в умовах інклюзивної освіти в загальноосвітніх закладах України [Training of specialists to work with children in the conditions of inclusive education in general educational institutions of Ukraine]. - Potapchuk, Tatiana; Kushnir, Valentyna (Kultura-Społeczeństwo-Edukacja, 2023)
The article proves the urgency of introducing inclusive education in general educational institutions; the system of vocational training of future primary school teachers in conditions of inclusive education is analyzed. The article actualizes that one of the prerequisites for Ukraine’s entry into a single European educational space is the introduction of European norms in education and science. The need for improving the Ukrainian education system, raising its level of quality is an important task, which is conditioned by the need to create positive conditions for the formation and realization of the student as a future professional and his personal self-realization. The solution of this problem is possible with the preparation of a future teacher with deep knowledge, has developed pedagogical abilities, perfect professional skills, professional self-awareness, pedagogical thinking, has the skills of self-education, self-improvement. Therefore, the formation of the readiness of the future teacher of an elementary school for professional work in modern conditions acquires special significance.